Use of Artificial Intelligence (AI) in the Workplace Ergonomics of Industry 5.0 - Maja Trstenjak; Tihomir Opetuk; Goran Đukić; Hrvoje Cajner (Tehnički Glasnik)
Industry 5.0 emphasizes human-centricity, sustainability, and resilience as its core characteristics, with a focus on developing socio-technical systems that enhance human health, safety, and well-being while fostering sustainable societal practices. The human-centric perspective places significant importance on human factors and ergonomics, aiming to align technological advancements with the needs and capabilities of individuals. In this context, artificial intelligence (AI) emerges as a transformative tool for advancing human factors and ergonomics by optimizing workplace conditions and supporting human-centered design principles. This paper conducts a literature review to explore the applications and potential of AI in addressing human factors and ergonomics challenges, providing insights into its role in shaping the future of human-centric systems within Industry 5.0.